Nonlinear characterization of the piecewise structural effects on whirl flutter of a rotor-nacelle system - Quintana, A.; Saunders, B. E.; Vasconcellos, R. [UNESP]; Abdelkefi, A. (American Institute of Aeronautics and Astronautics (AIAA), 2022)
Whirl flutter is an aeroelastic instability affected by structural or/and aerodynamic nonlinearities commonly found in rotor-driven aircraft. This instability may lead to destructive and potentially dangerous structural behaviors. A nonlinear reduced-order model for a nacelle-rotor system, using quasi-steady aerodynamics, is employed in this study. Several polynomial nonlinearities considering a two degrees-of-freedom nacelle-rotor model are tested to research the possible structural nonlinear effects in the presence of discontinuities, including combinations with symmetric cubic hardening nonlinearities for the pitch and yaw degrees of freedom, yaw nonlinearity, and pitch nonlinearity. Preliminary results show that the initial gap size used for discontinuities largely affects the bifurcation diagrams resulting in a variation in the critical flutter velocity as well as an effective change to the oscillation amplitudes. The characterization of the different existing jumps and transitions and their dependence to the environmental conditions or initial conditions will be deeply investigated and discussed. The effects of the gap size and stiffness will be explored on the dynamical responses of these rotor-nacelle based systems. A particular focus will be paid on the interaction between the freeplay nonlinearity and inherent structural nonlinearities in the degrees of freedom of the system.